Development of a Portfolio Strategy in Learning to Write Expositional Essays in Grade XI Students of SMA Negeri 3 Samarinda - Noviar, Iwan (Educationist: Journal of Educational and Cultural Studies, 2022)
The ability to write expository essays of students is still unsatisfactory and needs to be improved. The reason is that students are less interested in writing skills and the strategies used by teachers are still lacking. The portfolio strategy is expected to improve the ability to write exposition essays for class XI students. This study aims to determine whether there is an effect of portfolio assessment and feedback on learning Indonesian, especially learning to write exposition essays using a portfolio strategy. The research design used a classroom action research design with the research subject being the development of portfolio strategies in teaching exposition essay writing for class XI students. This research consisted of two cycles, each cycle consisting of planning, action, observation, and reflection. The data from this study were obtained using test instruments or in the form of exposition and non-test essays. Analysis of test data using quantitative techniques, while analysis of non-test data using qualitative techniques. Based on the analysis of research data, students' ability to write exposition essays from cycle I to cycle II has increased. The average score in writing expository essays from cycle I to cycle II has increased. The average value in writing expository essays in the first cycle was 5,42 and in the second cycle it increased by 2,62 with an average value of 8,03. So, the increase in the ability to write expository essays from cycle I to cycle II is 27,5%.